Reflecting on socially transformative environmental literacy for Lesotho - Tsepo Mokuku; Eureta Janse van Rensburg (Environmental Association of Southern Africa, 1997)
This paper is an attempt to clarify the concept of environmental literacy from a socially transformative orientation. It resulted from our ongoing reflection on a conceptual framework in and for a three-year research project on education for environmental literacy within the integrated science curriculum in Lesotho.